2011
DOI: 10.5539/elt.v4n1p156
|View full text |Cite
|
Sign up to set email alerts
|

On the Interaction of Test Washback and Teacher Assessment Literacy: The Case of Iranian EFL Secondary School Teachers

Abstract: It is by now well established that teacher characteristics play a major role in the way high stakes tests impact education (Alderson and Hamp-Lyons 1996). What remains an open question, however, is specifying the type of characteristics that have the potential to moderate the backwash effects of tests. This study was designed to isolate the effects of teachers’ assessment literacy in moderating the washback effects of summative tests in the EFL context of Iran. A test of assessment literacy and a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 14 publications
(5 reference statements)
1
24
0
Order By: Relevance
“…There are various kinds of factors which play crucial roles in the way tests affect education (Alderson and Hamp-Lyons, 1996). What remains a question, however, is specifying the factors that have a potential to moderate the washback effects of test (Razavipour, Riazi and Rashidi, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There are various kinds of factors which play crucial roles in the way tests affect education (Alderson and Hamp-Lyons, 1996). What remains a question, however, is specifying the factors that have a potential to moderate the washback effects of test (Razavipour, Riazi and Rashidi, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The novice teachers were found not to be confident in assessment and experienced teachers (who were usually older) were not familiar with recent technology-based types of asessment. Kiomrs, Abdolmehdi, and Rashidi (2011) designed a study and investigated the impact of teachers' assessment literacy on the washback effects of summative tests. The study was conducted with 53 secondary school teachers (male and female) in the public sector.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies focused on teachers' assessment knowledge and its effect on assessment procedure when we look at the international sphere. In the study of Kiomrs, Abdolmehdi and Naser (2011), it was found that Iranian EFL teachers have poor knowledge of language assessment, so they use standardized tests as they only know them as sources for assessment. Their exams were a copy of a standardized test with or without change.…”
Section: Language Assessment Literacymentioning
confidence: 99%